Media and entertainment industry management : how to integrate business and management with creativity and imagination - Ryu, Sunghan (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"Media and entertainment industry (MEI) significantly differs from traditional industries in many aspects. Accordingly, management of strategy, marketing, and other business practices in MEI necessitates a unique approach. Ryu offers students focused and relevant insights into critical topics with vivid examples from the industries. Unlike typical introductory textbooks on business and management, this book does not overemphasize complicated layers of theory. Instead, it presents essential concepts and frameworks in a digestible manner and supplements them with opportunities to apply this knowledge to real-world cases. The textbook demonstrates how knowledge can be constructively implemented in business and management scenarios, and is structured into 12 chapters, categorized under five core modules: (1) Overview of MEI, (2) Fundamentals of Management, (3) Marketing Management, (4) Digital Business and Management, and (5) New Business Model and Entrepreneurship. Students will gain the ability to explain key concepts and frameworks across core business and management domains and develop analytical skills through diverse real-world cases in MEI. Based on knowledge and skills, they will be equipped to identify management-related issues in the industries and generate practical and effective solutions. An essential guide for students who wish to understand business and management in the dynamic world of MEI"--
Overview of media and entertainment industry -- Marketing management -- Digital business and management -- New business model and entrepreneurship.
Keywords: Mass media -- Management; Internet entertainment industry -- Management; BUSINESS & ECONOMICS / Industries / Media & Communications Industries; BUSINESS & ECONOMICS / International / Marketing